Water Quality Responses to Accumulation of Microcystis During Cyanobacterial Bloom Event in Different Littoral Vegetation Zones of Lake Taihu, China - Xiang, Su-Lin; Zhu, Meng-Yuan; Zhu, Guang-Wei; Xu, Hai (Asian Journal of Chemistry, 2014)
To investigate the effects of bloom accumulation on water quality in different lake vegetation zones, we studied the physicochemical properties and nutrient levels during a bloom event in lake Taihu, China, using high-frequency field observations in an open water control zone, a floating plant zone dominated by Trapa bispinosa and Nymphoides peltatum and an emergent vegetation zone dominated by Phragmites australis. The results show that the emergent plant zone was much more susceptible to bloom accumulation. However, the bloom dispersed more slowly in the floating plant zone than in the emergent plant zone. At all sites, bloom accumulation led to significant increases in total nitrogen, total phosphorus and dissolved nutrients concentrations. High levels of nutrients accumulated more readily and dispersed more slowly in the floating plant zone than in the emergent plant zone. In later stages of the observation, blooms retained and affect dissolved nutrients. Therefore, the degree of bloom accumulation and the effect of bloom decomposition on nutrient levels varied significantly in different littoral vegetation zones. Littoral vegetation type is an important indicator to algal blooms for the implementation of ecological restoration strategies